Management of Haemarthrosis in Patients On Oral Anticoagulants. (17th February 2022) - Dalrymple, James; Davies, Andrew; Biggs, Alexandra; Rajcoomar, Shahil; Gill, Ian
Aims: Our aim was to investigate the management of patients who were admitted to hospital with an acute haemarthrosis whilst taking oral anticoagulants, and highlight the outcomes of different management strategies. Methods: A retrospective review was performed of all orthopaedic admissions over a 42-month period (January 2015-July 2018) to the Orthopaedic Department of a London District General Hospital. All patients admitted with a spontaneous joint haemarthrosis and concomitant use of oral anticoagulants was identified. Anonymised data was placed on a secure trust database. Findings: A total of 31 patients were included. 22 patients (71%) had their anticoagulant temporarily held during admission. 9 patients (29%) had their anticoagulation reversed with 10 mg of vitamin K. In 5 patients the haemarthrosis was aspirated either on admission or during their hospital stay. The overall mean length of stay in patients with a haemarthrosis was 6.8 days (median 3 days). There was no significant difference in length of stay when patients' anticoagulation was held compared to when the anticoagulation was continued. No patients suffered a thrombotic event in the 60 days following discharge. No adverse events were recorded following joint aspiration. Conclusion: Continuing patients' anticoagulants did not increase the length of hospital stay in this study, no thrombotic events were recorded. There is currently no consensus on the management of haemarthrosis in patients on oral anticoagulants. Further research may focus on assessing the effect of management adjuncts on patient outcomes to aid the development of clinical guidelines.